A primer on critical thinking and business ethics : recent conceptualizations of critical thinking. - Mascarenhas, Oswald A. J.; Thakur, Munish; Kumar, Payal, 1966- (Emerald Publishing Limited, 2023)
Encapsulating new developments in Critical Thinking skills for MBA students, in the form of a broad-based cross disciplinary primer in business management, with a special focus on business ethics.